Perception and Adoption of Upland Cropping Systems in South-East Cambodia - Tara, Pin; Sarom, Men; Thavarak, Huon; Sophoanrith, Ro; Kong, San; Bustamam, Hendri (Jurnal AGRISEP, 2024)
A survey was carried out to assess the opportunities and barriers for farmers to adopt intercropping and crop rotations in the uplands of Prey Veng and Svay Rieng provinces in South-Eastern of Cambodia. Survey methods with  37 respondents in Prey Veng and 39 respondents in Svay Rieng.  Epidata Software was used to build a data entry template and the data was further exported into SPSS Software for final cleaning and analysis. Each province has differences in agricultural cultivation and crop types. Majority of agricultural land is owned by farmers in Prey Veng province at 78.4% and Svay Rieng province at 74.4%, while rental land is 21.6-25.6%. The practices of crop rotation and intercropping systems is very low, crop rotation at 5.1-13.5% and intercropping at 2.6-5.4%. Own land ownership and practices of crop rotation/intercropping in Prey Veng province are higher than in Svay Rieng province. Obstacles to the adoption of intercropping between provinces are different, in Svay Rieng Province are lack of access to irrigation, lack of access to markets, labor and credit; while in the province of Svay Rieng are small field size, lack of market, lack of land ownership and lack of credit. In both provinces is the suitability of the technologies to the region and the high level of complexity. The barriers to adoption, especially lack of markets, labour and credit suggest the need for greater engagement of the private sector for the provision of advice and support.